Conservative treatment of patients with bladder genital tract fistula: Three case reports. Issue 31 (31st July 2020) - He, Zhiwei; Cui, Lifeng; Wang, Jia; Gong, Fengyan; Jia, Guifeng
Abstract: Introduction: Most of the patients with bladder genital tract fistula recover with surgical treatment. In the present study, we aimed to assess conservative treatment strategies for bladder genital tract fistula. Patient concerns: We reviewed 3 cases with bladder genital tract fistula who underwent treatment at our hospital from January to June 2017. Patient 1 underwent cesarean delivery, Patient 2 underwent total abdominal hysterectomy bilateral salpingo-oophorectomy (TAHBSO) and pelvic lymphadenectomy, and Patient 3 underwent extensive TAHBSO and pelvic lymphadenectomy. All 3 patients exhibited involuntary vaginal fluid outflow (average duration, 12.7 days; range, 7–21 days). Diagnosis: Patient 1 was diagnosed as vesicouterine fistula by cystosonography and Patient 2, Patient 3 was diagnosed as vesicovaginal fistula by cystoscopy. Interventions: All 3 patients underwent indwelling urinary catheterization. Outcomes: No vaginal fluid outflow could be observed after treatment of all 3 patients. Conclusion: Indwelling urinary catheterization should be administered for suitable patients as conservative treatment. If vesicouterine fistulas that are simple and have a diameter of <0.5 cm can be treated conservatively. If the condition does not resolve after 2 months, surgery should be considered.